A Preliminary Statement on Neo-Eskimo Occupations in Western Coronation Gulf, N.W.T. - Morrison, David (ARCTIC, 1981)
Excavations undertaken in 1980 in the western Coronation Gulf area, arctic Canada, are described. Work concentrated on the Clachan site (NaPi-2), a small Thule winter village. Stylistic analysis of the artifacts recovered suggests affiliation with Alaskan rather than Canadian Thule, despite a comparatively recent date for the site. Also briefly described are two "protohistoric" Copper Inuit sites.